Caught in a “mousetrap”: An analysis of the relationship of the local population with the Chornobyl Exclusion Zone in film and television productions (1990–2021) - Fiorito, Claudia (Studia Rossica Posnaniensia, 2024)
The release of the television series Chernobyl (HBO, Sky Atlantic 2019) drew renewed attention to the tragedy, its locations, and the affected population, generating new productions in Russia, such as the film Chernobyl: Abyss (Danila Kozlovskij, 2021), explicitly made in response to the Western series, signalling a desire to re-appropriate the narrative of the disaster and its territories. Indeed, a recurrent characteristic of the film and television productions of the countries most affected by the 1986 nuclear disaster (Ukraine, Belarus, and Russia) has been the representation of the land and the inhabitants’ relationship with it (Lindbladh 2019). This is also a central theme in Svetlana Alexievich’s renowned 1997 work Voices from Chernobyl: Chronicle of the future, whose stories inspired some episodes of the Anglo-American series. This article analyzes the representation of the relationship between the inhabitants of the Chornobyl/Chernobyl Exclusion Zone and their homeland in film and television productions dedicated to the nuclear disaster, beginning with Eastern European films made in the early 1990s, moving on to the representation in the Western series, and culminating with an analysis of Kozlovskij’s Chernobyl: Abyss. Features considered include the development of romantic narratives within the contaminated zone, the visual representation of radiation, and the depiction of the local institutions’ response to the disaster.